2016
DOI: 10.1007/s10753-016-0451-y
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin Inhibits IL-1β-Induced Inflammatory Response by Activating PPAR-γ in Human Osteoarthritis Chondrocytes

Abstract: Inflammation has been reported to play critical roles in the development of osteoarthritis. In the present study, we investigated whether mangiferin (MFN) had anti-inflammatory effects in IL-1β-stimulated human osteoarthritis chondrocytes. The cells were treated with various concentrations of MFN in the presence or absence of IL-1β. The production of MMP-1, MMP-3, PGE2, and NO was measured in this study. The expression of NF-kB and PPAR-γ was detected by western blot analysis. MFN inhibited IL-1β-induced infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…Some natural compounds, such as dioscin (a saponin), and mangiferine (a xanthone glucoside), have up-regulated another isoform, PPARγ in osteoarthritic cartilage and chondrocytes. Dioscin protects the cartilage by antioxidant, anti-apoptotic, and anti-inflammatory effects that down-regulate the canonical Wnt pathway, while mangiferine inhibits IL-1β-induced PGE2 release, canonical NFκB signaling, and activation of MMP-1, and MMP-3 [114,115]. In summary, PPAR molecules are protective for osteoblasts and interfere with multiple cellular pathways, implicating both members of the Wnt family and OPG.…”
Section: Metabolic Regulator Pparβ/δ Is a Putative Link Between Omentioning
confidence: 99%
“…Some natural compounds, such as dioscin (a saponin), and mangiferine (a xanthone glucoside), have up-regulated another isoform, PPARγ in osteoarthritic cartilage and chondrocytes. Dioscin protects the cartilage by antioxidant, anti-apoptotic, and anti-inflammatory effects that down-regulate the canonical Wnt pathway, while mangiferine inhibits IL-1β-induced PGE2 release, canonical NFκB signaling, and activation of MMP-1, and MMP-3 [114,115]. In summary, PPAR molecules are protective for osteoblasts and interfere with multiple cellular pathways, implicating both members of the Wnt family and OPG.…”
Section: Metabolic Regulator Pparβ/δ Is a Putative Link Between Omentioning
confidence: 99%
“…In high-fat diet (HFD)-fed obese rats, injection of mango leaf tea, the main component of which is mangiferin, markedly downregulated serum TG and TC levels, with obvious amplification of PPARγ expression in adipose tissue [17]. In addition, Qu et al [18] identified that mangiferin diminished interleukin-1β (IL-1β)-induced NF-κB activation and production of matrix metalloproteinase-1 (MMP-1) and MMP-3 in human osteoarthritis chondrocytes by activating PPARγ. In this paper, we designed experiments to elucidate whether mangiferin exerts hypolipidemic effects via stimulation of the PPARγ-LXRα-ABCA1/G1 pathway, which likely mitigates atheromatous plaque formation in apoE -/- mice.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that LPS could contribute to low-grade cell inflammation (Huang and Kraus, 2016), while OA is exactly the low-grade inflammatory state mentioned above. Besides, previous investigations have demonstrated that MF was a xanthonoid with anti-inflammatory capacity, and it was reported to be a promising therapeutic drug for OA (Luczkiewicz et al, 2014;Saha et al, 2016;Qu et al, 2017b;Garrido-Suarez and Garrido, 2019). Previous investigations elucidated that MF markedly suppressed the productions of IL-6, IL-1b, and TNF-a in LPS-triggered primary hepatocytes, BALB/c mice mammary gland, and peritoneal macrophages (Jeong et al, 2014;Pan et al, 2016;Qu et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%